IMPROVING SUSTAINABLE COMPETITIVE ADVANTAGE OF CREATIVE INDUSTRY THROUGH STRATEGIC ALLIANCES TO OVERCOME ENVIRONMENTAL TURBULENCE (International Conference of Graduate School on Sustainability (ICGSS), 2018)
Fundamental changes in the business environment that cause turbulence are suspected making many companies difficult to maintain competitive advantage. To restore competitive advantage, MSEs, need to take strategic steps through strategic alliance that is the most appropriate approach to an increasingly turbulent environment.This study aims to examine the effect of strategic alliances as mediating variables in the relationship between environmental turbulence and sustainable competitive advantage. The design of this study uses 130 craft industries. Data collection was conducted in all region of Malang Raya including Malang Regency, Malang City and Batu City.The findings show that environmental turbulence does not a significant relationship with sustainable competitive advantage but has a significant relationship with strategic alliance. Strategic alliance has a significant relationship with sustainable competitive advantage. Strategic alliance will mediate the relationship environmental turbulence and sustainable competitive advantage. The analysis showed that highly environmental turbulence tended to highly strategic alliance. The result of the study show that strategic alliance practiced by SMEs has been significantly affected the sustainable competitive advantage. It indicated that strategic alliance offers a systematic model for supporting SMEs to build a well-maintained environment and sustainable competitive advantage